2015
DOI: 10.1097/prs.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Grading Instruments

Abstract: Facial nerve grading scales intend to provide objectivity and uniformity of reporting to otherwise subjective analysis. The Facial Nerve Grading Scale 2.0 requires further evaluation for intraobserver reliability. The Sunnybrook Facial Grading Scale has been robustly evaluated with respect to the criteria prescribed in this article. Although sophisticated technology-based methodologies are being developed for potential clinical application,the authors recommend widespread adoption of the Sunnybrook Facial Grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
112
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 213 publications
(119 citation statements)
references
References 52 publications
1
112
0
Order By: Relevance
“…This study showed that a modified version of the S-FGS-the mS-FGS, including evaluation of the DLI and DAO muscles-significantly improved the overall assessment of facial nerve dysfunctions following parotidectomy. Several other instruments are available to clinically assess facial nerve impairments 9,15,16 . The most popular is the House-Brackmann Facial Nerve Grading System (HB), which grades the facial nerve function in six levels 17 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study showed that a modified version of the S-FGS-the mS-FGS, including evaluation of the DLI and DAO muscles-significantly improved the overall assessment of facial nerve dysfunctions following parotidectomy. Several other instruments are available to clinically assess facial nerve impairments 9,15,16 . The most popular is the House-Brackmann Facial Nerve Grading System (HB), which grades the facial nerve function in six levels 17 .…”
Section: Discussionmentioning
confidence: 99%
“…It offers a regional assessment, considering the face at rest and during movements, beyond the synkinesis, and with good intraobserver and interobserver reliability. 9 The five standard expressions cover the temporal, zygomatic and buccal branches. However, muscles predominantly innervated by the MMB are not included in the system, limiting the test's use for post-parotidectomy assessment (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations